The Effect of Store Image, Store Atmosphere, Product Variation and Location on Purchasing Decisions - Firliyani, Indah; Hidayah, Arini; Miftahuddin, Muchammad Agung; Rahmawati, Ika Yustina (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research seeks to examine the influence of Store Image, Store Atmosphere, Product Variety, and Location on the Purchasing Decisions of consumers at Central Fashion Store Purbalingga. This study uses quantitative methods with data collection through questionnaires. Using simple random sampling involving 120 respondents. The data analysis technique uses SPSS 20. The results showed that store image has a positive but insignificant effect on purchasing decisions. Store atmosphere, product variety, and location have a positive and significant effect on purchasing decisions. The results of this study can help Central Fashion Store Purbalingga to improve its operational strategies, especially in terms of store image, store atmosphere, product variety, and location, in order to maintain consumer purchasing decisions.